Coincident Electron Channeling and Cathodoluminescence Studies of Threading Dislocations in GaN. (12th November 2013) - Naresh-Kumar, Gunasekar; Bruckbauer, Jochen; Edwards, Paul R.; Kraeusel, Simon; Hourahine, Ben; Martin, Robert W.; Kappers, Menno J.; Moram, Michelle A.; Lovelock, Stephen; Oliver, Rachel A.; Humphreys, Colin J.; Trager-Cowan, Carol
Abstract We combine two scanning electron microscopy techniques to investigate the influence of dislocations on the light emission from nitride semiconductors. Combining electron channeling contrast imaging and cathodoluminescence imaging enables both the structural and luminescence properties of a sample to be investigated without structural damage to the sample. The electron channeling contrast image is very sensitive to distortions of the crystal lattice, resulting in individual threading dislocations appearing as spots with black–white contrast. Dislocations giving rise to nonradiative recombination are observed as black spots in the cathodoluminescence image. Comparison of the images from exactly the same micron-scale region of a sample demonstrates a one-to-one correlation between the presence of single threading dislocations and resolved dark spots in the cathodoluminescence image. In addition, we have also obtained an atomic force microscopy image from the same region of the sample, which confirms that both pure edge dislocations and those with a screw component (i.e., screw and mixed dislocations) act as nonradiative recombination centers for the Si-doped c-plane GaN thin film investigated.